The Influence of MILI Digital Payment Service Quality on Partner Satisfaction using the Servqual Method - Ricky Rivaldo; Yopi Handrianto (Information Technology and Systems, 2025)
This study investigates the influence of service quality dimensions on partner satisfaction with MILI Digital Payment, a fintech application developed by PT Jendela Prima Indonesia in 2019. MILI provides digital transaction services such as prepaid credit, internet packages, bill payments, and ticket reservations, primarily targeting micro, small, and medium enterprises (MSMEs). Despite its benefits, user complaints regarding system disruptions, limited customer service, and ineffective feature socialization highlight potential service quality issues. This research adopts a causal-associative quantitative approach using the Servqual framework, which measures service quality across five dimensions: tangible, reliability, responsiveness, assurance, and empathy. Data were collected from 100 active MILI partners in Bekasi through purposive sampling and analyzed using multiple linear regression in SPSS, following validity, reliability, and classical assumption tests. Results demonstrate that, simultaneously, all five dimensions significantly affect partner satisfaction. However, responsiveness emerges as the only dimension with a significant partial effect, suggesting that timely responses and problem-solving play a critical role in shaping satisfaction. The findings contribute both theoretically and practically by confirming the applicability of Servqual in fintech contexts and providing strategic insights for improving digital service performance. Limitations include the study’s geographic focus on Bekasi and its restricted variables. Future research is recommended to expand the scope and explore additional factors such as trust and usability.